2015
DOI: 10.1113/jphysiol.2014.280792
|View full text |Cite
|
Sign up to set email alerts
|

Short‐chain fatty acid sensing in rat duodenum

Abstract: Key pointsr Luminal lipid in the duodenum modulates gastroduodenal functions via the release of gut hormones and mediators such as cholecystokinin and 5-HT. Abstract Intraduodenal fatty acids (FA) and bacterial overgrowth, which generate short-chain FAs (SCFAs), have been implicated in the generation of functional dyspepsia symptoms. We studied the mechanisms by which luminal SCFA perfusion affects duodenal HCO 3 − secretion (DBS), a measure of mucosal neurohumoral activation. Free fatty acid receptor (FFAR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 51 publications
(124 reference statements)
5
79
0
Order By: Relevance
“…In accordance with the expression profile of FFA2 and FFA3, stimulation of enteroendocrine cells with SCFAs can trigger GLP-1 (Reimer and McBurney, 1996;Lin et al, 2012;Tolhurst et al, 2012;Nøhr et al, 2013;Psichas et al, 2015), GLP-2 (Akiba et al, 2015), peptide tyrosine tyrosine (Lin et al, 2012;Psichas et al, 2015), and GIP (Lin et al, 2012) release. However, reports as to whether oral SCFAs can increase enteroendocrine hormones in vivo are mixed.…”
Section: Physiologic Roles Of Ffa2/ffa3mentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the expression profile of FFA2 and FFA3, stimulation of enteroendocrine cells with SCFAs can trigger GLP-1 (Reimer and McBurney, 1996;Lin et al, 2012;Tolhurst et al, 2012;Nøhr et al, 2013;Psichas et al, 2015), GLP-2 (Akiba et al, 2015), peptide tyrosine tyrosine (Lin et al, 2012;Psichas et al, 2015), and GIP (Lin et al, 2012) release. However, reports as to whether oral SCFAs can increase enteroendocrine hormones in vivo are mixed.…”
Section: Physiologic Roles Of Ffa2/ffa3mentioning
confidence: 99%
“…One study found oral SCFAs had no effect on GLP-1, but decreased the plasma GIP response to glucose challenge (Tang et al, 2015). FFA2 agonists may also act on enterochromaffin cells to trigger 5-hydroxytryptamine release, which together with GLP-2 would help prevent mucosal injury (Akiba et al, 2015), suggesting a mechanism for the benefits to adding SCFAs to total parenteral nutrition. Finally, there is a link between SCFAs and decreased intestinal motility, which is FFA3-and neuroendocrine-independent (Dass et al, 2007).…”
Section: Physiologic Roles Of Ffa2/ffa3mentioning
confidence: 99%
See 1 more Smart Citation
“…Propionic acid produced by propionic acid bacteria is also present in BGS [22]. SCFA receptors, especially GPR41, are expressed in gastrointestinal hormone-producing endocrine cells of the stomach and duodenum as well as the jejunum, ileum and colon [23,24]. Propionic acid and/or butyric acid derived from fermented milk products and BGS in PF may promote GLP-1 production in the upper gastrointestinal tract via GPR41.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the rat proximal duodenum possesses an active short-chain fatty acid (SCFA) absorption mechanism and that luminal SCFAs stimulate duodenal bicarbonate secretion via SCFA receptors (FFA2 and FFA3) and SCFA transporter-dependent pathways (Figure 2) [65;66]. Luminal SCFA acetate increases the secretory rate of bicarbonate through FFA2-mediated 5-HT release and FFA3-mediated GLP-2 release, consistent with results of studies in which selective FFA agonists were used singly [23;67*].…”
Section: Tuft Cellsmentioning
confidence: 99%